2009
DOI: 10.1111/j.1476-5381.2009.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of ibuprofen and diclofenac with aspirin in healthy volunteers

Abstract: Background and purpose: Aspirin reduces the risk of myocardial infarction and stroke by inhibiting thromboxane production in platelets. This inhibition can be competitively antagonized by some non-steroidal anti-inflammatory drugs (NSAIDs). Experimental approach: By measuring thromboxane B2 production in healthy volunteers, we investigated whether ibuprofen (800 mg three times daily for 7 days) or diclofenac (50 mg three times daily for 7 days) taken concurrently with aspirin 80 mg (once daily for 7 days) infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 20 publications
1
34
0
3
Order By: Relevance
“…In contrast to the unanimous conclusions of the in vitro studies, in vivo studies depict a more complicated picture. Schujit et al looked at the interaction between oral diclofenac and aspirin by measuring serum thromboxane B 2 levels in healthy volunteers . These volunteers received aspirin 80 mg once daily with oral diclofenac 50 mg 3 times a day for 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the unanimous conclusions of the in vitro studies, in vivo studies depict a more complicated picture. Schujit et al looked at the interaction between oral diclofenac and aspirin by measuring serum thromboxane B 2 levels in healthy volunteers . These volunteers received aspirin 80 mg once daily with oral diclofenac 50 mg 3 times a day for 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…The antiplatelet effects of aspirin may be decreased due to co-administration of ibuprofen [3, 10, 11], and a warning is included in the package inserts of both aspirin and ibuprofen. When ibuprofen binds with COX-1, it hinders acetylation of the serine residue by aspirin [3].…”
Section: Introductionmentioning
confidence: 99%
“…Catella-Lawson et al (22) demonstrated that the antiplatelet effect of aspirin is attenuated if ibuprofen is administered up to 12 h after enteric-coated aspirin administration. Data are less clear with other NSAIDs but are suggestive in total that nonselective NSAIDs (e.g., indomethacin, naproxen) also interfere with the antiplatelet effects of aspirin in a similar manner as ibuprofen, whereas use of more COX-2 selective agents (e.g., celecoxib, diclofenac, meloxicam) likely do not interfere with aspirin (27)(28)(29). Thienopyridine P2Y 12 inhibitors.…”
Section: Antiplateletsmentioning
confidence: 96%